Crystalline fragments in glasses - Antonio, Giomal A. [UNESP]; Kalia, Rajiv K.; Nakano, Aiichiro; Vashishta, Priya (American Physical Society (APS), 1992)
The nature of tetrahedral molecular fragments is investigated in SiSe2 glasses using the molecular-dynamics method. The glass consists of both edge-sharing (ES) and corner-sharing tetrahedra. The ES tetrahedra are the building blocks of chain-like-molecular fragments. The two-edge-sharing tetrahedra are the nucleus, and corner-sharing configurations provide connecting hinges between fragments. Statistics of rings and fragments reveals that threefold and eightfold rings are most abundant, chainlike fragments that are typically 1015 long occur mostly in eightfold rings, and the longest fragments occur in elevenfold rings. © 1992 The American Physical Society.